Analisis Capital Asset Earning dan Liquidity dalam Menilai Kinerja Keuangan Bank Tabungan Negara Periode 2006-2010 - Siagian, Pariang (Binus Business Review, 2012)
To communicate the financing performance of a bussines includes banking operation by companyâs management to many users can be doing by severals tools or mediums. And one of them is financial statement. In that statements we can assess or evaluate all of its bussines activities. By doing analizing to the financial statements its might shown us about how the company using of all the financial resources to achieve their determined plans. The objectives of this article is how to get the informations about the financial performance of Bank Tabungan Negara by doing Financial Statements analysis from the year 2006 to 2010.